2019
DOI: 10.1055/s-0039-1678688
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided de Quervain's Tendon Release, Feasibility, and First Outcomes

Abstract: Background de Quervain's syndrome is one of the main tendonitis of the wrist. The hypothesis of authors was that de Quervain's syndrome could be successfully treated with a specific ultrasound-guided percutaneous procedure, as it is for trigger finger. Surgical Technique Identification of the subcompartmentalization of the first extensor compartment was performed first, using the Hiranuma's classification, prior to the surgery. Then, we assessed precisely the positions of the sensory branches of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…We put forward a different point of view from other studies (9)(10)(11). Due to two volar bony ridges in the radial styloid process (24), the extensor retinaculum fixes the two tendons here, and the narrow area formed by the bony bulge and tendon sheath enlarges the stress of tendon.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We put forward a different point of view from other studies (9)(10)(11). Due to two volar bony ridges in the radial styloid process (24), the extensor retinaculum fixes the two tendons here, and the narrow area formed by the bony bulge and tendon sheath enlarges the stress of tendon.…”
Section: Discussionmentioning
confidence: 94%
“…Research demonstrates that the first annular pulley's percutaneous release procedures produce outcomes comparable to those of open surgery in the trigger finger (8). According to three studies, dQD may be treated efficiently and safely using percutaneous release technology (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…In the cadaveric portion, they found that successful complete release of the FDC was performed in 13 of 14 wrists, and the single case of incomplete release was in a wrist where a separate EPB subcompartment had not been identified on US; they found superficial tendon abrasions in some cases, but otherwise there were no injuries to the surrounding structures. In their case series, PNR was performed in the office, and they found decreased DASH scores at 1 month, with 19 of 22 patients returning to work by 3 months 67 . While some of the data reported in these studies are encouraging, higher-level studies regarding PNR are needed before this procedure should be considered a legitimate treatment option.…”
Section: Operative Managementmentioning
confidence: 96%
“…Their study also included a prospective case series of 35 patients who underwent PNR, and they found that 91.4% of patients had a negative Finkelstein test at 1 month, had marked improvements in outcome measures at up to 6 months following the procedure, and were able to avoid surgical release 66 . Croutzet et al also performed a cadaveric study that was followed by a prospective case series 67 . In the cadaveric portion, they found that successful complete release of the FDC was performed in 13 of 14 wrists, and the single case of incomplete release was in a wrist where a separate EPB subcompartment had not been identified on US; they found superficial tendon abrasions in some cases, but otherwise there were no injuries to the surrounding structures.…”
Section: Operative Managementmentioning
confidence: 99%
“…[60][61][62][63] Although studied in a small group of cadavers/patients, US-guided release in patients with DQD has been reported as a safe and reliable procedure, without any specific morbidity. 64…”
Section: Exemplary Evidencementioning
confidence: 99%